2017
DOI: 10.1152/ajpheart.00553.2016
|View full text |Cite
|
Sign up to set email alerts
|

Activation of PPAR-α in the early stage of heart failure maintained myocardial function and energetics in pressure-overload heart failure

Abstract: Failing heart loses its metabolic flexibility, relying increasingly on glucose as its preferential substrate and decreasing fatty acid oxidation (FAO). Peroxisome proliferator-activated receptor α (PPAR-α) is a key regulator of this substrate shift. However, its role during heart failure is complex and remains unclear. Recent studies reported that heart failure develops in the heart of myosin heavy chain-PPAR-α transgenic mice in a manner similar to that of diabetic cardiomyopathy, whereas cardiac dysfunction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 23 publications
6
50
0
Order By: Relevance
“…In several different models of cardiac fibrosis, fenofibrate prevented interstitial and perivascular cardiac fibrosis, through a mechanism that involved reduced endothelin-1 levels (Ogata et al, 2002, 2004; Iglarz et al, 2003; Diep et al, 2004; LeBrasseur et al, 2007; Forcheron et al, 2009; Zhang et al, 2016). Similar results were observed using inducible overexpression of PPARα early in the progression of pressure overload-induced cardiac damage (Kaimoto et al, 2016). However, one study using fenofibrate treatment of chronic pressure overload in PPARα knockout mice showed that fenofibrate had profibrotic effects that were independent of PPARα (Duhaney et al, 2007).…”
Section: Peroxisome Proliferator-activated Receptorssupporting
confidence: 81%
“…In several different models of cardiac fibrosis, fenofibrate prevented interstitial and perivascular cardiac fibrosis, through a mechanism that involved reduced endothelin-1 levels (Ogata et al, 2002, 2004; Iglarz et al, 2003; Diep et al, 2004; LeBrasseur et al, 2007; Forcheron et al, 2009; Zhang et al, 2016). Similar results were observed using inducible overexpression of PPARα early in the progression of pressure overload-induced cardiac damage (Kaimoto et al, 2016). However, one study using fenofibrate treatment of chronic pressure overload in PPARα knockout mice showed that fenofibrate had profibrotic effects that were independent of PPARα (Duhaney et al, 2007).…”
Section: Peroxisome Proliferator-activated Receptorssupporting
confidence: 81%
“…Intensive studies over the past two decades have begun to uncover the staggering complexity of metabolic regulation directed by a plethora of cross-activating transcription factors, including nuclear receptor family members (12,13,(32)(33)(34). Dynamic interactions between these factors orchestrate metabolic remodeling in response to various physiological and pathophysiological stimuli (35)(36)(37)(38)(39)(40). Prominent among these factors is the transcriptional coactivator PGC-1α, which acts as a master regulator of mitochondrial oxidative metabolism by coordinating the capacity of each step required for ATP synthesis (20).…”
Section: Discussionmentioning
confidence: 99%
“…Energy metabolism has become the promising therapeutic targets for HF [6]. HF is characterized by dysfunction of generating adenosine triphosphate (ATP) to maintain cardiac contractility due to the metabolic imbalance of fatty acid (FA) and glucose metabolisms [7]. In the healthy circumstances, fatty acid oxidation (FAO) is the major resource of ATP [6].…”
Section: Introductionmentioning
confidence: 99%